Paleo-sea-level indicators in the Southern Tyrrenian Sea: Insights into relative sea-level changes from the Last Glacial Maximum to the early Holocene - M. Corradino; C. Cirelli; V. Di Donato; D. Melini; F. Molisso; G. Spada; D. Casalbore; F. Pepe (Marine Geology, 2026)

Slip-rates and time recurrences of the seismogenic Sant’Eufemia normal fault (SE Tyrrhenian Sea), a multiscale and multidisciplinary approach - M.F. Loreto; L. Capotondi; D.D. Insinga; F. Molisso; L. Vigliotti; S. Albertazzi; P. Giordano; F. Muto; S. Romano (Marine and Petroleum Geology, 2023)

Liquefied sites of the 2012 Emilia earthquake: a comprehensive database of the geological and geotechnical features (Quaternary alluvial Po plain, Italy) - L. Minarelli; S. Amoroso; R. Civico; P. M. De Martini; S. Lugli; L. Martelli; F. Molisso; K. M. Rollins; A. Salocchi; M. Stefani; G. Cultrera; G. Milana; et al. (Bulletin of Earthquake Engineering, 2022)
This paper presents a comprehensive geological and geotechnical study of the whole area affected by liquefaction following the 2012 Emilia earthquakes, including all the available information from the field reconnaissance surveys, in situ tests, and laboratory analyses. The compilation was performed at 120 liquefied sites to verify and validate the reliability of liquefaction charts in alluvial sediments, and to assess liquefaction induced by the 2012 seismic sequence in the Emilia plain. The results reveal a wide range of grain sizes (from clean sands to sandy silts) and compositional characteristics (quartz-rich to litharenitic) in the 2012 ejecta, and show a strong relationship between the liquefaction and stratigraphic architecture of the subsurface. The availability of in situ tests at the liquefied sites makes it possible to verify and validate the reliability of the liquefaction charts in alluvial sediments with respect to the real observations. For the analyzed Emilia case studies, the use of non-liquefiable crust provides better estimations of the liquefaction manifestations when coupled with the thickness of the liquefiable layer rather than with the liquefaction potential index. Altogether, this work makes available to the international scientific community a consistent liquefaction database for in-depth earthquake studies.

The Late Holocene tephra record of the central Mediterranean Sea: Mapping occurrences and new potential isochrons for the 4.4–2.0 ka time interval - D. D. Insinga; P. Petrosino; I. Alberico; G. J. de Lange; C. Lubritto; F. Molisso; M. Sacchi; R. Sulpizio; J. Wu; F. Lirer (Journal of Quaternary Science, 2020)
Five cores from the southern Tyrrhenian and Ionian seas were studied for their tephra and cryptotephra content in the 4.4–2.0 ka time interval. The chronological framework for each core was obtained by accelerator mass spectrometry 14 C dating, the occurrence of distinct marker tephra and stratigraphic correlation with adjacent records. Tephrochronology allowed us to correlate the analyzed deposits with tephra markers associated with Somma‐Vesuvius (79 ad ), Ischia Island (Cretaio), Mt Etna (FG, FL and FS) and Campi Flegrei (Astroni‐Agnano Monte Spina) events. For the first time in the marine setting, a large single glass data set is provided for the Late Holocene Etnean marker beds including the FS tephra (ca. 4.3 ka). Moreover, unknown deposits from Lipari (ca. 2.2–2.0 ka) and Vulcano (3.6–3.3 ka) are also recognized at more distal sites than previously reported. These results contribute to improve the high‐resolution tephrostratigraphic framework of the central Mediterranean Sea. They also provide new insights into the chemical composition and dispersal pattern of tephras that can be used as inter‐archive tools for regional and ‘local’ stratigraphic correlations and for addressing paleoclimate research.